2009
DOI: 10.1007/s11276-009-0186-x
|View full text |Cite
|
Sign up to set email alerts
|

An optimal new-node placement to enhance the coverage of wireless sensor networks

Abstract: Wireless sensor networks provide a wide range of applications, such as environment surveillance, hazard monitoring, traffic control, and other commercial or military applications. The quality of service provided by a sensor network relies on its coverage, i.e., how well an event can be tracked by sensors. This paper studies how to optimally deploy new sensors in order to improve the coverage of an existing network. The best-and worst-case coverage problems that are related to the observability of a path are ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…This method redefines sensor nodes to reduce coverage holes and improve network coverage, saves energy consumption, and guarantees connectivity while limiting sensor mobile costs. By comparing with other deployment methods, it is found that this method can improve network coverage and reduce the mobile costs of WSNs [8].…”
Section: Deployment Methodsmentioning
confidence: 99%
“…This method redefines sensor nodes to reduce coverage holes and improve network coverage, saves energy consumption, and guarantees connectivity while limiting sensor mobile costs. By comparing with other deployment methods, it is found that this method can improve network coverage and reduce the mobile costs of WSNs [8].…”
Section: Deployment Methodsmentioning
confidence: 99%
“…Aziz et al, 2009;Hou et al, 2010). However, for DSNs, these two geometric structures have not drawn much attention of researchers on the field coverage issues.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when it is required to reduce the length of the longest edge (i.e., the maximum transmission range) in a bottleneck path between two transceivers, s and t, in an existing network consisting of n transceivers, by adding k new transceivers. See [11,12,16] for more applications in sensor networks.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the EBST problem, the EBSP problem is solvable in polynomial time. Ignoring (only for now) the dependence on k, Hou et al [11] gave an O(n 2 log n))-time exact algorithm for the problem, based on a binary search in the set of all potential lengths (of the longest edge). In this paper, we show that it suffices to consider a certain subset of potential lengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation